A DESIGN OF THE NONLINEAR ADAPTIVE CONTROL SYSTEM FOR PH NEUTRALIZATION PROCESS IN WASTEWATER TREATMENT INSTALLATIONS OF BATIK INDUSTRY - Nazuwatussya'diyah
Public interest and market in batik have grown since UNESCO designated it as a World Cultural Heritage. However, problems arise when the proper batik wastewater treatment is not considered while developing the batik sector and causing environmental pollution. One critical parameter that often harms the environment of biota, water, plants, and industry is the degree of acidity (pH). The dyeing and dyeing process in batik waste, which generates acidic and alkaline waste and contains color, contributes to pH properties. The pH value in the range of 6 – 9 has meet the waste quality standard based on the Decree of the Minister of Environment No. 5 of 2014. Mold will form if the pH level is too low, and bacteria will compete with each other to break down organic metabolism. On the other hand, microbial will be inhibited when the pH level is too high. Therefore, it is necessary to have a water treatment plant for the batik industry. This study will be carried out to design a nonlinear adaptive control system for the pH neutralization process at the Wastewater Treatment Plant (WWTP) of the Batik Industry. The laboratory scale of WWTP plant is designed with a 1.5 m × 0.75 m × 1 m size with a capacity of 87.75 liters and modular type tank. Three primary processes are integrated into the WWTP: equalization, neutralization, and adsorption. The neutralization pH process is the main process and focus of this study to lower the pH of the waste through a chemical reaction between the strong NaOH alkaline and weak acid neutralizer CH3COOH. The neutralizing solution flows to the neutralization tank using a peristaltic pump with a range of 10-100ml/ minute. The WWTP panel is also designed to be 40 cm × 30 cm × 15 cm to integrate instrumentation and control to facilitate system control and monitoring. This panel uses four Arduino microcontrollers: one master and three slaves. This study applies the 12C protocol as data communication between Arduino, connecting the SDA, SCL, and GND pins of each Arduino to facilitate the distribution of data. In this study, a design of a nonlinear adaptive control system for the pH neutralization process in the Batik Industrial WWTP has been done. Based on Lyapunov’s theory, stable results are obtained from the control law; therefore, simulations are carried out using the Ordinary Differential Equation (ODE) function in MATLAB software to estimate all parameters of the pH neutralization process. The results of open-loop experiments on the 9.5 pH waste in a simulation can reach pH 7 in 7,549 seconds with a neutralizer flow rate parameter value of 0.1940/60 L/s, a waste flow rate of 1/60 L/s, and a neutralizer concentration of 0.001 M. Meanwhile, it takes longer time (18,697 seconds) to reach pH 7 in implementation and reach steady state condition at pH 6.5 in 23,275 seconds but still within the permissible pH limits. The results of the open look implementation were then identified as a first-order system process with a time delay, with process parameter values including the time constant ????= 4813,09 seconds, the delay ????????= 13000,35 seconds, the gain ????= 15.43 and sse = 61.44. Identification of this system aims to obtain suitable PI parameters by Ziegler Nichols tuning, and it was found that the value of ????????=?58121 × 10-5 and ????????=?2,4251 × 10-2. The ???????? and ???????? values will be used in the microcontroller program for PI controller calculations. The PI controller was compared to the adaptive controller used in this study. In the simulation, closed loop pi of pH 9 waste can reach pH 7 in 2613 seconds while in the adaptive closed loop with control parameters value ????= 8, ????1= 20, and ????2= 40 can reach pH 7 faster, which is 2041 seconds. Similar to the implementation results, the neutralization time for closed loop pi is 18,528 and 17,834 seconds, and 17.041 and 8,998 seconds for the adaptive closed loop. In conclusion, the experimental results have a shorter time to reach neutral pH with the application of adaptive control compared by using the PI control or open loop control.